Assessment of Worldwide Acute Kidney Injury Epidemiology in Neonates: Design of a Retrospective Cohort Study - Jetton, Jennifer G.; Guillet, Ronnie; Askenazi, David J.; Dill, Lynn; Jacobs, Judd; Kent, Alison L.; Selewski, David T.; Abitbol, Carolyn L.; Kaskel, Fredrick J.; Mhanna, Maroun J.; Ambalavanan, Namasivayam; Charlton, Jennifer R.; et al. (Frontiers in Pediatrics, 2016)
INTRODUCTION: Acute kidney injury (AKI) affects 30% of hospitalized neonates. Critical to advancing our understanding of neonatal AKI is collaborative research among neonatologists and nephrologists. The Neonatal Kidney Collaborative (NKC) is an international, multidisciplinary group dedicated to investigating neonatal AKI. The AWAKEN study (Assessment of Worldwide Acute Kidney injury Epidemiology in Neonates) was designed to describe the epidemiology of neonatal AKI, validate the definition of neonatal AKI, identify primary risk factors for neonatal AKI, and investigate the contribution of fluid management to AKI events and short term outcomes. METHODS and ANALYSIS: The NKC was established with at least one pediatric nephrologist and neonatologist from 24 institutions from 4 countries (USA, Canada, Australia, India). A Steering Committee and four subcommittees were created. The database subcommittee oversaw the development of the web-based database (MediData Rave™) that captured all NICU admissions from 1/1/14-3/31/14. Inclusion and exclusion criteria were applied to eliminate babies with a low likelihood of AKI. Data collection includes: 1) baseline demographic information; 2) daily physiologic parameters and care received during the first week of life; 3) weekly “snapshots”; 4) discharge information including growth parameters, final diagnoses, discharge medications and need for renal replacement therapy; and 5) all serum creatinine values. ETHICS and DISSEMINATION: AWAKEN was proposed as human subjects research. The study design allowed for a waiver of informed consent/parental permission. NKC investigators will disseminate data through peer-reviewed publications and educational conferences. DISCUSSION: The purpose of this publication is to describe the formation of the NKC, the establishment of the AWAKEN cohort and database, future directions and a few “lessons learned”. The AWAKEN database includes 325 unique variables and >4 million discrete data points. AWAKEN will be the largest, most inclusive neonatal AKI study to date. In addition to validating the neonatal AKI definition and identifying risk factors for AKI, this study will uncover variations in practice patterns related to fluid provision, renal function monitoring, and involvement of pediatric nephrologists during hospitalization. The AWAKEN study will position the NKC to achieve the long-term goal of improving the lives, health and well-being of newborns at risk for kidney disease.